Useful life lessons for health and well-being: adults’ reflections of childhood experiences illuminate the phenomenon of the inner child - Sjöblom, Margareta (Int J Qual Stud Health Well-being, 2018)
Purpose: The aim of this study was to describe and gain more knowledge about the phenomenon of the inner child in relation to health and well-being reflected in events during childhood experienced by adults. Method: In this hermeneutical phenomenological study, 20 adults, 10 men and 10 women aged 22–68, were interviewed. Results: The analysis of the data illuminated the phenomenon of the inner child in one theme: Gaining useful life lessons through childhood experiences, made up by four sub-themes: Sharing relationships, playing to heal, being strong or frail and supporting the next generation. Conclusion: The participants’ experiences of events during childhood were illuminating the phenomenon of the inner child as promoting or hindering health and well-being and impact human adaptation throughout life. Our findings indicate that the participants learned useful life lessons suggesting that experiences during childhood can help us to adapt across the life span and over generations, and this is the essence of the inner child. Our findings also contribute to the health literacy discussion and detail how knowledge and action competency is developed in mental, social and existential dimensions of health and well-being.